2021
DOI: 10.3390/ijms22094943
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Tackle Antimicrobial Resistance: The Example of Escherichia coli and Pseudomonas aeruginosa

Abstract: Traditional antimicrobial treatments consist of drugs which target different essential functions in pathogens. Nevertheless, bacteria continue to evolve new mechanisms to evade this drug-mediated killing with surprising speed on the deployment of each new drug and antibiotic worldwide, a phenomenon called antimicrobial resistance (AMR). Nowadays, AMR represents a critical health threat, for which new medical interventions are urgently needed. By 2050, it is estimated that the leading cause of death will be thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 157 publications
(192 reference statements)
0
17
0
Order By: Relevance
“… This table is based on the following references for vaccines ( Merakou et al., 2018 ; Bianconi et al., 2019 ; Theuretzbacher et al., 2020 ; Sainz-Mejías et al., 2020 ; Micoli et al., 2021 ; Antonelli et al., 2021 ), antibodies ( Lakemeyer et al., 2018 ; Theuretzbacher et al., 2020 ; Adlbrecht et al., 2020 ; Yaeger et al., 2021 ; Zurawski and McLendon, 2020 ), polymyxins ( Li, et al., 2019 ; Theuretzbacher et al., 2020 ; Lepak et al., 2020 ), new antibiotics ( WHO, 2021 ; Dickey et al., 2017 ; Tse et al., 2017 ), new combinations of β-lactam/β-lactamase inhibitor ( WHO, 2021 ; Theuretzbacher et al., 2020 ), phages ( Friman et al., 2016 ; Jault et al., 2019 ; Patil et al., 2021 ), iron metabolism disruption ( Zhang et al., 2021 ; Frei et al., 2020 ), anti-biofilm ( Dickey et al., 2017 ), and other anti-virulence factors ( Dickey et al., 2017 ; Theuretzbacher et al., 2020 ). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… This table is based on the following references for vaccines ( Merakou et al., 2018 ; Bianconi et al., 2019 ; Theuretzbacher et al., 2020 ; Sainz-Mejías et al., 2020 ; Micoli et al., 2021 ; Antonelli et al., 2021 ), antibodies ( Lakemeyer et al., 2018 ; Theuretzbacher et al., 2020 ; Adlbrecht et al., 2020 ; Yaeger et al., 2021 ; Zurawski and McLendon, 2020 ), polymyxins ( Li, et al., 2019 ; Theuretzbacher et al., 2020 ; Lepak et al., 2020 ), new antibiotics ( WHO, 2021 ; Dickey et al., 2017 ; Tse et al., 2017 ), new combinations of β-lactam/β-lactamase inhibitor ( WHO, 2021 ; Theuretzbacher et al., 2020 ), phages ( Friman et al., 2016 ; Jault et al., 2019 ; Patil et al., 2021 ), iron metabolism disruption ( Zhang et al., 2021 ; Frei et al., 2020 ), anti-biofilm ( Dickey et al., 2017 ), and other anti-virulence factors ( Dickey et al., 2017 ; Theuretzbacher et al., 2020 ). …”
Section: Discussionmentioning
confidence: 99%
“…A novel approach such as reverse vaccinology combined with genomic technologies has recently been described in P. aeruginosa , identifying potentially surface-exposed immunogenic proteins relevant in pathogenesis ( Bianconi et al., 2019 ). The use of outer membrane vesicles, because it carries many surface antigens that can serve as targets, also represents a promising approach for vaccine development ( Antonelli et al., 2021 ).…”
Section: Vaccines: a Prophylactic Strategy For High-risk Patientsmentioning
confidence: 99%
“…To date, several antigens have been nominated as vaccine candidates 32 , 33 . Although no clinical trials have been conducted for the vaccine candidates against A. baumannii , some vaccine and passive immunization candidates against P. aeruginosa are in phase 2/3 of clinical trials 33 , 34 . Recent advances in active and passive immunization against A. baumannii 33 , 35 – 38 as well as recent clinical trials in the case of P. aeruginosa 33 , 34 revealed that immunization trials are among the most promising resolves against these notorious nosocomial pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Although no clinical trials have been conducted for the vaccine candidates against A. baumannii , some vaccine and passive immunization candidates against P. aeruginosa are in phase 2/3 of clinical trials 33 , 34 . Recent advances in active and passive immunization against A. baumannii 33 , 35 – 38 as well as recent clinical trials in the case of P. aeruginosa 33 , 34 revealed that immunization trials are among the most promising resolves against these notorious nosocomial pathogens. However, despite numerous efforts carried out to develop effective vaccines against A. baumannii 36 , 38 – 45 and P. aeruginosa 46 51 , no approved vaccine is yet available.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, in the case of Shigella, the required genetic modification is the deletion of tolR gene, encoding for a protein involved in the linking of inner and outer membranes (Bereswill et al, 2012;Rossi et al, 2014). GMMA represent an attractive vaccine technology (Rietschel et al, 1991;Schromm et al, 2000;Bereswill et al, 2012;Rossi et al, 2014;Mancini et al, 2020;Micoli and MacLennan, 2020;Antonelli et al, 2021;Fiorino et al, 2021), as they can naturally express the same bacteria antigens or can be carriers of protein antigens or polysaccharides to induce a specific immune response (Bereswill et al, 2012;Kis et al, 2019;Mancini et al, 2021). GMMA stimulate innate immune cells, as they are able to provide innate signals via ligands of toll-like receptors (TLRs) and via pathogen-associated molecular patterns (PAMPs) (Mancini et al, 2020).…”
Section: Introductionmentioning
confidence: 99%